Implementation of Invesment Based Sales Growth (IBSG) on Asset Improvement - Siti Puryandani; Oktavian Yodha Utama (Journal of Management and Entrepreneurship Research, 2020)
Objective: This study examines the effect of implementation of invesment based sales growth (IBSG) on asset improvement in the food and beverages companies from 2017 to 2019. In this research, IBSG consist of tangible asset, company’s growth, positioning, liquidity, sales performance, business risk, firm size, profitability, and tax. Asset Improvement reflected to capital structure which proxy is debt to total asset ratio. Research Design & Methods: The sample is taken according to purposive sampling with the criteria, finally 21 companies are taken from 31 companies. The data were examined with the assistance of SPSS21 software. Data collected from the company's financial statements and measured using a formula adopted from earlier research. Findings: tangible assets have a significant positive effect on capital structure, company’s growth has a significant negative effect on capital structure, positioning has a significant positive effect on capital structure, liquidity has a significant positive effect on capital structure, sales performance has no effect on capital structure, business risk has no effect on capital structure, firm size has a significant positive effect on capital structure, profitability has a significant positive effect on capital structure, an tax has a significant positive effect on capital structure. Limitations & Recommendations: R square value is low, then suggessted to add more variables for future research. the number of company samples is too small, then recommanded to add more period in future research. Contribution & Value Added: This result contributes to the financial literature, especially related to the companies listed in food and beverages companies group. Practically, stakeholders can use this result as additional information in making policy decisions.